Cyanobacteria-Pesticide Interactions and Their Implications for Sustainable Rice Agroecosystems - Sadhana Yadav; Rupanshee Srivastava; Nidhi Singh; Tripti Kanda; Ekta Verma; Piyush Choudhary; Shivam Yadav; Neelam Atri (International Journal of Microbiology)
Modern agricultural practices rely heavily on fertilizers and pesticides to boost crop yields, essential for feeding the growing global population. However, their extensive use poses significant environmental risks. Chemical-based fertilizers and pesticides persist in ecosystems, potentially harming ecological stability. Wetland rice farming utilizing nitrogen-fixing cyanobacteria has emerged as an ecofriendly alternative, drawing attention due to its capacity to mitigate pesticide-related issues. Cyanobacteria, capable of fixing atmospheric nitrogen, thrive in low-nitrogen conditions and can aid plant growth. Some species can also biodegrade pesticides, offering a means to clean up contaminated environments. Researchers are exploring ways to leverage cyanobacteria’s nitrogen fixation and biodegradation abilities for ecofriendly biofertilizers and environmental cleanup. This approach presents promise for sustainable agriculture and environmental preservation. The current study delves into multiple studies to investigate global pesticide usage levels, primary categorization, and persistence patterns. It also investigates cyanobacterial distribution and their interactions with pesticides in wetland rice ecosystems, aiming to enable their use in sustainable agriculture. Additionally, the review provides a thorough summary of the literature’s findings about the potential of cyanobacteria in pesticide degradation.